Rooting of blackberry (Morus nigra L.) cuttings treated with natural extracts of coco-grass (Cyperus rotundus L.) and lentil (Lens culinaris Medik) (Research, Society and Development, 2023)
The genus Morus L. is composed of approximately 24 species, in which the species Morus nigra is one of the best known. The experiment objective was to evaluate the rooting level of blackberry cuttings treated with two natural inducers, tiririca and lentils. The experiment was conducted in the greenhouse of the Faculty of Natural Sciences, Lúrio University in Mozambique in Western Africa, between May and August 2019. The experimental design was entirely randomized with 4 treatments and 5 repetitions. The treatments were composed: T0- witness; T1- coco-grass extract; T2- lentil extract and T3- lentil extract 50% + coco-grass extract 50%. At 90 days the percentage of rooting of cuttings, root formation per cuttings, number of rooted cuttings, survival index and average root length were evaluated. The data obtained were analysed for normality by W Shapiro-Wilk test. The statistical analyses were performed using the statistical program SISVAR. The tested treatments did not influence the rooting of blackberry cuttings, that is, there were no significant differences among the treatments. Coco-grass extract showed values always higher than the other extracts in the following variables: root formation per cuttings, number of sprouted cuttings, survival index, except for average root length. Research like this constitutes a new data, being necessary future studies on the rooting profile of the species Morus nigra L.